Impact of quality of life (QoL) on glycemic control (HbA1c) among adolescents and emerging adults with long‐duration type 1 diabetes: A prospective cohort‐study. Issue 8 (30th January 2017) - Stahl‐Pehe, Anna; Landwehr, Sandra; Lange, Karin S.; Bächle, Christina; Castillo, Katty; Yossa, Rhuphine; Lüdtke, Jana; Holl, Reinhard W.; Rosenbauer, Joachim
Abstract : Objective: To evaluate the impact of self‐reported chronic‐generic and condition‐specific quality of life (QoL) on glycemic control among adolescents and emerging adults with long‐duration type 1 diabetes (T1D) in a longitudinal design. Methods: The database used was a nationwide cohort study of patients with ≥10 years T1D duration at baseline in Germany. The baseline questionnaire survey was conducted in 2009‐2010, the follow‐up survey in 2012‐2013; additional clinical data of routine care procedures were linked. QoL was assessed by the DISABKIDS chronic generic module (DCGM‐12) and diabetes module (DM) with treatment and impact scales. Regression analyses were conducted for the outcome hemoglobin A1c (HbA1c) at follow up with baseline DISABKIDS scores as predictors and sociodemographic and health‐related covariates. Results: At baseline, the included 560 patients had a mean age of 15.9 (SD 2.3) years, a diabetes duration of 13.0 (2.0) years, and an HbA1c of 67 (14.2) mmol/mol. Mean follow‐up time was 3.0 (0.6) years. Univariate analyses indicated associations between baseline QoL scores and HbA1c at follow‐up (β[DCGM‐12] = −0.174 (SE 0.038), β[DM treatment] = −0.100 (0.022), β[DM impact] = −0.177 (0.030), p < .001). The associations remained significant after adjustment for sociodemographic and illness‐related factors, but dissolved (p > .60) when additionally adjusting for baseline HbA1c. In patients with poor baseline HbA1c (>75 mmol/mol), significant associations were observed between DCGM‐12 and DM impact scores and follow‐up HbA1c (β[DCGM‐12] = −0.144 (0.062), p = .021; β[DM impact] = −0.139 (0.048), p = .004). Conclusions: QoL was inversely associated with HbA1c after 3 years in the course of T1D only in patients poorly controlled at baseline.